Development and validation of a high throughput system for discovery of antigens for autoantibody detection. - Isabel K Macdonald (Public Library of Science (PLoS), 2012)
An assay employing a panel of tumor-associated antigens has been validated and is available commercially (EarlyCDT®-Lung) to aid the early detection of lung cancer by measurement of serum autoantibodies. The high throughput (HTP) strategy described herein was pursued to identify new antigens to add to the EarlyCDT-Lung panel and to assist in the development of new panels for other cancers. Two ligation-independent cloning vectors were designed and synthesized, producing fusion proteins suitable for the autoantibody ELISA. We developed an abridged HTP version of the validated autoantibody ELISA, determining that results reflected the performance of the EarlyCDT assay, by comparing results on both formats. Once validated this HTP ELISA was utilized to screen multiple fusion proteins prepared on small-scale, by a HTP expression screen. We determined whether the assay performance for these HTP protein batches was an accurate reflection of the performance of R&D or commercial batches. A HTP discovery platform for the identification and optimal production of tumor-associated antigens which detects autoantibodies has been developed and validated. The most favorable conditions for the exposure of immunogenic epitopes were assessed to produce discriminatory proteins for use in a commercial ELISA. This process is rapid and cost-effective compared to standard cloning and screening technologies and enables rapid advancement in the field of autoantibody assay discovery. This approach will significantly reduce timescale and costs for developing similar panels of autoantibody assays for the detection of other cancer types with the ultimate aim of improved overall survival due to early diagnosis and treatment.